Klasztor kraśnicki od fundacji w 1468 roku do reformy w 1618 roku - Łatak, Kazimierz (Archiwa, Biblioteki i Muzea Kościelne, 2017)
The Kraśnik monastery of the Canons Regular in the years 1468-1618 was one of the most important centres of religious and cultural life in the Lublin region. Although there were hardly ever more than twelve monks in the monastery, it was the interior character of the monastery and its exterior activity that increased its importance and role in civilization. The monks conducted their mission through prayer, broadly understood pastoral work, science and education, the promotion of culture and art, almsgiving and various economic initiatives. In pursuit of holiness and apostolate, they encountered both glories and successes, which are reflected in buildings, works of art, books, forms of piety, and monks who rendered great service to the Church and Poland. There were also failures, which in many cases were conditioned by external events such as natural disasters, wars and other circumstances. For the people living nearby, the monastery was always a reference point, contributing to the spiritual, intellectual and material culture of the town and its surroundings, which today is a part of not only Polish and ecclesial but also European Christian civilization. The author presented an outline of the history of the monastery of the Canons Regular in Kraśnik in the first period of its existence, that is from its beginning to 1618. He addressed the following issues: the staffing of the monastery, the organization of monastic life, their pastoral commitment, their contribution to the culture of the region and the finances of the monastery.